Use of Behavioral Cognitive-Based Innovative Creative Counseling to Prevent Student Bullying Behavior - Karneli, Yeni; Firman, Firman; Yusri, Nada Fristy; Iskandar, Arief Hakim (Universitas Negeri Padang, 2022)
Bullying is something that demages and hurts someone, both physically and psychologically. In the last few decades the phenomenon of bullying has gotten worse, causing problems for individuals, families, and the educational environment. Basically bullying is when someone does or says something on purpose, intended to hurt or embarrass another person. Bullying happens from time to time, and is ongoing. It rarely happens only once, besides bullying there is always someone who feels stronger (the perpetrator) and someone who is weaker (the victim). Victims of bullying experience many impacts, such as stress, skipping school, anxiety, depression and the desire to commit suicide. Therefore it is necessary to prevent student bullying behavior, one of which is the use of innovative creative counseling based on cognitive behavior. This writing aims to explore student bullying behavior and develop innovative creative counseling based on cognitive behavior. This writing uses the method of study literature. The results of this study indicate that cognitive-behavioral-based innovative creative counseling is effective for preventing student bullying behavior.